Internalization of Islamic Values in Children within Families in the Digital Era - Aziz, Thorik (Nak-Kanak: Journal of Child Research, 2024)
The digitalization of a wide range of information poses a significant challenge in the current era, especially concerning the integration of Islamic values in early childhood education. This research delves into the Islamic education of young children within familial settings during the digital age, utilizing a "library research" methodology. Generally, digital technology offers a dual-edged nature. The advantages of such technology lie in its capacity to simplify access to information and assist educators in creating digital-based educational content. However, on the downside, it also provides children with easier access to potentially harmful content that may be inappropriate for their age. Islamic education for young children in a family context during this digital epoch must address the evolving dynamics of the times while implementing positive and transformative approaches. To achieve this, several initiatives can be adopted within the family: developing an understanding of child growth stages, being informed of the educational content being conveyed, particularly regarding Islamic teachings, mastering the ability to regulate the digital platforms frequently accessed by children, and leveraging digital media as a valuable tool for education within the home setting. This research contributes an understanding and methodology for preserving Islamic values within the family sphere while navigating the complexities of the digital age. It highlights the importance of balancing technological advancements with foundational religious teachings in early childhood instruction.